Knowledge - sharing behaviour in software development organization - Lee, Sook Ling (2016)
The aims of this cross-sectional quantitative analysis include examining the influence of attitude, subjective norms and perceived behavioural control on knowledge-sharing behaviour among information technology professional at software development organizations, besides identifying the most influential variables as well as the moderating effects of distributive justice. Self-administered questionnaires, which developed based on previous studies, were distributed to sample respondents from nine public listed software development organization and successfully yield 168 valid responses. Analysis shows a moderate tendency of knowledge-sharing behaviour among respondents. Further, Pearson Correlation analysis validated significant and positive relationships between the three independent variables and knowledge-sharing. By comparison, subjective norms were the most influential factors on the said behaviour while perceived behavioural control accounted the least variance on knowledge-sharing behaviour among respondents. Overall, introduction of distributive justice had moderated these relationships. Such results revealed detrimental implications on the organization and information technology professionals, which direct to justifications on the emergence of such phenomenon besides some suggestions for improvement. Finally, some suggestions for future researches are identified and proposed, serves as the conclusion of this study.